DIVERSIFICATION OF ENVIRONMENTAL POLICY INSTRUMENTS FROM THE PERSPECTIVE OF INTEGRATED POLICYMAKING - Vucic, Vlastimir; Radović Vučić, Miljana (The European Journal of Applied Economics, 2020)
Most severe societal issues that are crosscutting the boundaries of established jurisdiction connect the incompatible objectives of economic competitiveness, social development, and environmental protections with the concept of SDI. The conventional environmental policy domain is unable to achieve environmental objectives by itself and each policy sector must take into consideration and integrate environmental objectives if they are anyhow to be achieved. Within the context of the present research, the energy sector is very important due to how the EU governs its energy-related issues, also due to more explicit reasons such as the CO2 emission reductions, economic impacts, and energy security, as well as due to the potential of RES-E. The lack of clarity on how the integration of environmental concerns or objectives into energy policy has transformed and modified energy policy is the main reason behind the modest levels of integrated policy-making in the energy sector achieved and it is the reason why the present research attempts to clarify how the integrated policymaking adds value to the diversification of environmental policy instruments and inclusion or integration of environmental concerns or objectives into the policy domain of energy.
Keywords: Sustainable development (SD); Environmental policy integration (EPI); Renewable electricity (RES-E); Policy instruments; Integrated policymaking